Maritime Geopolitical Strategy For Strengthening The Security of North Natuna Marine Waters Against - Wijaya, Dwi Ayuni; Jurianto, Moch; Suwarno, Panji; Widodo, Pujo; Saragih, Herlina Risma Juni; Kristijarso, Kristijarso (PT FORMOSA CENDEKIA GLOBAL, 2024)
The North Natuna Sea is rich in marine resources, especially fish, and is part of Indonesia's Exclusive Economic Zone (EEZ). Illegal, unreported, and unregulated fishing (IUU fishing) in the North Natuna Sea region has become a crucial issue affecting Indonesia's maritime sovereignty and security. This article examines maritime geopolitical strategies that can be implemented to reduce fish theft in the region. The method used in this research is a qualitative method with a literature study to explore maritime geopolitical strategies to strengthen the security of the North Natuna Sea waters against IUU fishing. The proposed approach includes enhancing maritime defense capabilities, regional cooperation, and maritime diplomacy. In addition, monitoring and law enforcement are also the main focus.